Jogo, dança e brincadeira na educação física: experiências lúdico-sociais na área de linguagens - Lourenço, Fabio Tadeu da Silva (Universidade Federal de São Carlos, 2026)
This research presented an intervention proposal that sought to integrate Play, Dance, and Games in Physical Education, highlighting the thematic unit of body language and students' social interactions. The proposal aimed to analyze the contributions of playfulness, mediated by body language, in the teaching and learning process of School Physical Education in the early years of Elementary School. In this sense, the research brought to the discussion the Common National Curriculum Base (BNCC), the Curriculum of the City of São Paulo, and guiding documents from the Municipal Government of São Paulo, as well as legislation for pedagogical guidance and the investigation framework. The research was conducted with a 2nd-grade class of Elementary School from a municipal public school in São Paulo/SP, under the supervision of the teacher-researcher himself. The adopted methodology was qualitative in nature, observing the cultural manifestations and prior knowledge of the students, as well as their local reality. Data collection was carried out through field notes with the aim of capturing experiences, interactions, and perceptions of the activities conducted throughout the 12 lessons of the teaching unit. Analytical categories were presented, along with pedagogical procedures related to teaching methodology and physical education as a space for language, socialization, and communication. It is noteworthy that the approach involving games, dances, and playground activities proved to be of utmost importance for the learning process, and that the active participation of students throughout the course significantly contributed to the understanding of the historical, social, and cultural dimensions of these practices, broadening reflection on body culture, identity, belonging, and collective forms of expression. It is noteworthy that the approach to games, dances, and play proved to be extremely important for the learning process, and that the active participation of students throughout the developed path significantly contributed to the understanding of the historical, social, and cultural dimensions of these practices, expanding reflection on bodily culture, identity, belonging, and collective forms of expression. Thus, the teaching unit made significant contributions to the cultural education of students by increasing contact with games, dances, and play as expressions of bodily culture, as well as to the improvement and qualification of future pedagogical practices in the field of school Physical Education. As a result, it was observed that the students began to understand games, dances, and play activities as expressions of bodily culture, recognizing these practices as legitimate and meaningful cultural productions. There was also greater engagement in the proposed activities, evidenced by active participation, interactions established among peers, and the use of body language as a form of communication and expression. It is noteworthy that the educational approach developed, based on experience and dialogue, contributed significantly to the understanding of the social, historical, and cultural dimensions of bodily practices, expanding the meanings attributed to play in the school context.
Game, dance, and play in physical education: playful-social experiences in the area of languages
Keywords: Jogo, dança e brincadeira; Linguagem Corporal; Ludicidade; Game, dance, and play; Body language; Playfulness; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade